Co‐evolution of coarse grain structuring and bed roughness in response to episodic sediment supply in an experimental aggrading channel. Issue 4 (16th January 2020) - Hassan, Marwan A.; Saletti, Matteo; Zhang, Chendi; Ferrer‐Boix, Carles; Johnson, Joel P.L.; Müller, Tobias; von Flotow, Claudia
ABSTRACT: We use flume experiments to better understand how gravel‐bed channels maintain bed surface stability in response to pulses of sediment supply. Bed elevations and surface imagery at high spatial resolutions were used to quantify the co‐evolution of surface grain‐size distribution (GSD), bed roughness statistics, and bed surface structures (clusters, cells and transverse features). Using a new semi‐automated method, we identified individual stone structures over a 2 m × 1 m area throughout the experiments. After an initial coarsening, surface GSD and armouring ratio remained nearly stable as sediment pulses caused net bed aggradation. In contrast, individual grain structures continued to form, increase or decrease in size, and disappear throughout the experiments. The response of the bed to sediment pulses depended on the history of surface roughness evolution and bed surface structure development, as these factors changed much more in response to supply perturbations earlier in the experiments compared to later, even as the bed continued to aggrade. We interpret that the dynamic production and destruction of bed surface structures can act as a 'buffer' to sediment supply pulses, maintaining a stable bed surface during aggradation with minimal change in grain size or armouring. © 2019 John Wiley & Sons, Ltd. Abstract : We investigate riverbed surface evolution during aggradation in response to episodic sediment supply. Our results show that the response of the bed to sediment pulses depends on the history of the bed surface roughness and structure as these factors changed much more in response to supply perturbations earlier in the experiments. We interpret that thedynamic production and destruction of bed surface structures can act as a "buffer" to sediment supply pulses and maintaining a stable bed surface.